Situated Poetry Learning Using Multimedia Resource Sharing Approach - Yang, Che-Ching; Tseng, Shian-Shyong; Liao, Anthony Y. H; Liang, Tyne (Educational Technology ＆ Society, 2013)
Educators have emphasized the importance of situating students in an authentic learning environment. By using such approach, teachers can encourage students to learn Chinese poems by browsing content resources and relevant online multimedia resources by using handheld devices. Nevertheless, students in heterogeneous network environments may have different requirements for the resource subject, type, size, etc. The central issue of this study is how to locate appropriate resources to support situated learning based on user context. In an attempt to solve the primary concern, this study proposes a context-based dialogue approach with which students may interact to retrieve adequate poems and multimedia resources. The Poetry Multimedia Resource Index is the basis for the retrieval, which consists of outer lexical resources, multimedia resource information, and Chinese poems. A prototype system has been conducted to evaluate the effectiveness of the approach. The experimental group adopts the situated learning method by using this system, while those in the control group adopt the situated learning method by using textbooks. It is found that our approach can be significantly beneficial to promote students' learning achievements. The majority of students are satisfied with the proposed system and the teacher participant showed a positive attitude toward this system.